Non‐Conventional Electrochemical Techniques for Assembly of Electrodes on Glassy Carbon‐Like PPF Materials and Their Use in a Glucose Microfluidic Fuel‐Cell. Issue 6 (20th October 2014) - Dector, A.; Arjona, N.; Guerra‐Balcázar, M.; Esquivel, J. P.; Campo, F. J. Del; Sabaté, N.; Ledesma‐García, J.; Arriaga, L. G.
Abstract This paper addresses the electrochemical growth of PtAg and Au nanoparticles on pyrolyzed photoresist films (PPFs). The PtAg/PPF electrode was evaluated toward oxygen reduction reaction (ORR) in the absence and presence of glucose; meanwhile the electrocatalytic activity of Au/PPF was investigated for the glucose electrooxidation reaction (GOR) in 0.3 M KOH in the absence and presence of air as an oxygen source. The results obtained using the electrochemical studies showed that the PtAg/PPF electrode exhibited tolerance toward the ORR in the presence of low glucose concentrations. Moreover, Au/PPF showed good affinity toward glucose oxidation at high concentrations (50 and 100 mM) in the presence of oxygen instead further oxidations of glucose by‐products. Both electrocatalysts were evaluated as the cathode (PtAg/PPF) and the anode (Au/PPF) in a glucose microfluidic fuel cell (G‐μFC) constructed using a UV‐lithography technique and several sheets of different polymeric materials. The G‐μFC was tested using 100 mM glucose with 0.3 M KOH as electrolyte in the absence of an external source of nitrogen or oxygen as the fuel at zero flow rate; this cell reached a maximum power density of 0.085 mW cm−2 using a low Pt loading (approximately 20% of weight percentage) mixed with non‐noble materials, such as Ag.